The impact of organizational justice on job satisfaction, organizational commitment and trust - Hossein Azimi, Fatemeh Onagh, (Opción, 2019)
Current research tries to examine how the aspects of organizational justice and dimensions of its subset affect job satisfaction, organizational commitment, and organizational trust. Current research is descriptive in terms of data and it is survey research. Standard questionnaires were distributed randomly among 40 statistical samples. Data analysis with SPSS software showed that the distribution of data is normal. The Pearson correlation test was used for determining the relationship of variables. Results showed that all hypotheses of research are supported and there is a positive and significant relationship between organizational justice and job satisfaction, organizational commitment, and organizational trust.